Magical doors and digital gateways: exploring global connectivity and alienation in Mohsin Hamid's Exit West - M. Ahmed, Alshaymaa Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2025)
This paper analyses the metaphorical importance of magical doors in Mohsin Hamid's Exit West (2017) as a critique of digital technologies and their effects on global connectivity. The research adopts a comprehensive interdisciplinary approach, combining literary analysis with post-digital and globalisation theory, to reinterpret the magical doors as metaphors for digital tools such as social media and video communication platforms. Hamid reinterprets magical realism within a post-digital framework, examining the contradictions of hyperconnectivity. The magical doors offer the allure of immediate mobility and the breakdown of physical barriers, yet simultaneously reveal issues of emotional detachment, cultural disintegration, and instability. This study presents a noteworthy addition to the fields of literary studies and digital criticism, reinterpreting Exit West as an important reflection on the psychological and societal implications of technological globalisation. This research analyses the relationship between migration, identity, and belonging, offering fresh perspectives on the novel's critique of contemporary hyperconnectivity. The examination enhances interpretations of Hamid’s work and establishes it as an essential perspective for comprehending the wider human consequences of existing in a connected yet divided world.